EFEKTIVITAS PEMBERIAN POC KOTORAN BURUNG WALET TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Iyana Nasruddin; Fawzy Muhammad Bayfurqon; Yayu Sri Rahayu (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Onion production must always be increased. Liquid organic fertilizers affect the growth and development of soil microbes and the nutrients contained in POC will be absorbed more quickly by plants. Guano or swallow droppings originating from the swallow cultivator building are currently not widely used and further processed, even though the waste can be used as fertilizer that can fertilize plants. This study aims to obtain the POC dose of swallow droppings that provide the highest growth effectiveness and yield in shallot (Allium ascalonicum L.) plants.The research method used was a single factor Randomized Block Design (RBD), namely the dose of POC with 7 treatments that were repeated 4 times, namely treatment A (Without NPK and POC (control (-)), B (NPK 600 kg / ha (control (+)), C (POC 3 l / ha + NPK 300 kg / ha), D (POC 6 l / ha + NPK 300 kg / ha), E (POC 9 l / ha + NPK 300 kg / ha), F (POC 12 lt / ha + NPK 300 kg / ha), G (POC 15 l / ha + NPK 300 kg / ha). Data were analyzed using variance (ANOVA) and DMRT at the 5% level. Based on the results of the study, the dosage of swallow droppings POC did not have a significant effect on all components of growth and yield. This shows that POC made from swallow droppings has not been able to increase the growth and production of shallot plants.